2019
DOI: 10.3390/jcm8091414
|View full text |Cite
|
Sign up to set email alerts
|

The Risky Health Behaviours of Male Adolescents in the Southern Italian Region: Implications for Sexual and Reproductive Disease

Abstract: Recent epidemiological studies suggest an increase of sexual and reproductive chronic diseases caused by problematic behaviours acquired during peri-pubertal age. The aims of our study were: (i) to investigate awareness of sexual transmitted infections (STIs) among adolescents; (ii) to describe the close relationship between possibly incorrect lifestyles during adolescence and reproductive and sexual disturbances during adulthood. The “Amico-Andrologo” survey is a permanent nationwide surveillance program supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In the review by Cannarella et al, a general overview of pediatric varicocele is given, including a compelling flowchart reporting the management from an endocrinologic point of view [5]. Interestingly, a survey of the risky lifestyles for the reproductive and sexual function in male adolescents is provided by Perri et al [6]. Worryingly, this study reveals a non-negligible percentage of smokers, drinkers, and cannabis consumers among male adolescents.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In the review by Cannarella et al, a general overview of pediatric varicocele is given, including a compelling flowchart reporting the management from an endocrinologic point of view [5]. Interestingly, a survey of the risky lifestyles for the reproductive and sexual function in male adolescents is provided by Perri et al [6]. Worryingly, this study reveals a non-negligible percentage of smokers, drinkers, and cannabis consumers among male adolescents.…”
mentioning
confidence: 98%
“…As far the clinical aspects, childhood cancer [4], pediatric varicocele [5], and risky lifestyles [6] (including substance abuse [7]) are addressed in the current Special Issue. Duca et al […] evaluate the testicular function of childhood cancer survivors and address which cancer, therapy, and age of treatment has the worst reproductive outcomes in adulthood.…”
mentioning
confidence: 99%
“…This has led to the development of studies that have evaluated sperm parameters in late adolescence, as well as to estimate the prevalence of risky lifestyle for the andrological health in this population, such as smoke, alcohol, drug consumption, unprotected sexual intercourse, which highlights the importance of undergoing to andrological counseling in adolescence. Thus, dysmetabolism and risky lifestyle negatively interfere with male gonadal function at a young age and deserve fully attention [13][14][15][16]. Accordingly, recent studies have shown the detrimental impact of lifestyle factors on testicular function in adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another Italian study conducted in 360 male high-school students reported an elevated prevalence of cigarette smoke (41.5%), alcohol consumption (9.3%), and cannabis use (19.7%). Their overall awareness about the risk of STDs was low [ 15 ]. Finally, a longitudinal study prospectively evaluated the presence of correlations between insulin-resistance and non-alcoholic fatty liver disease (NAFLD) with TV and sperm parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation